2003
DOI: 10.3168/jds.s0022-0302(03)73815-6
|View full text |Cite
|
Sign up to set email alerts
|

Managing Manure Nutrients Through Multi-crop Forage Production

Abstract: Concentrated sources of dairy manure represent significant water pollution potential. The southern United States may be more vulnerable to water quality problems than some other regions because of climate, typical farm size, and cropping practices. Dairy manure can be an effective source of plant nutrients and large quantities of nutrients can be recycled through forage production, especially when multi-cropping systems are utilized. Linking forage production with manure utilization is an environmentally sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
0
32
2
Order By: Relevance
“…Grasses outperformed broad leafed forages in dry matter yields and nutrient uptake on application of animal manure. Grasses vary in their potential for removal of phosphorus from contaminated soils [14]. Other studies also indicate the usefulness of phytoremediation using stargrass [15] and perennial ryegrass [16] in phosphorus impacted soils.…”
Section: Introductionmentioning
confidence: 97%
“…Grasses outperformed broad leafed forages in dry matter yields and nutrient uptake on application of animal manure. Grasses vary in their potential for removal of phosphorus from contaminated soils [14]. Other studies also indicate the usefulness of phytoremediation using stargrass [15] and perennial ryegrass [16] in phosphorus impacted soils.…”
Section: Introductionmentioning
confidence: 97%
“…Nutrient removal from the soil may vary because of differences in biomass production, cultivars, weather, soil type, and management practices [42]. For example, Newton et al [36] showed that grasses have greater ability to absorb soil nutrients than broadleaf forages, implying that grasses differ in their potential to remove nutrients from the soil. Also, in a study comparing nutrient removal rates by perennial grasses, giant reed (Arundo donax L.) had the highest aboveground biomass yield and the highest nutrient (N, P, and K) concentrations and removal rates compared to switchgrass, giant miscanthus, weeping lovegrass [Eragrostis curvula (Shrad.)…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of manure in crop growing with appropriate agronomic management practices allows the opportunity to utilize the nitrogen produced by dairy farms for forage crop production [47]. Cultivation based on the use of manure in cropping management reduces the input of chemical fertilizers, increases the flow of nutrient cycling farmer and the sequestration of carbon in the Ap horizon [810].…”
Section: Introductionmentioning
confidence: 99%